KARAKTERISTIK PASAR MODAL DAN INSTRUMEN KEUANGAN NON RIBA - Bachruddin Bachruddin (Journal Competency of Business, 2017)
This working paper slated to introduce capital market characteristic terminological conventional view and Islam view. Besides is sighted too various prevalent financial instrument is commercialized at capital market and another finance market. Its appearance is Islamic stock price index at capital markets as New York (Dow Jones Islamic is Index), at Malaysia (islamic’s Boogy confluence Index), and at Jakarta (Islamic’s Jakarta Index) mark progressively financial institutional amends Islamic. Method that is used is studi empirical ala compare about capital market practice at state already goes forward notably at United States Of America and at state thet follow Islam economic system. A variety prevalent finance instrument is commercialized at capital market and Iainya’s finance market have gotten sharpness about criterion what is let or is prohibitted terminological islamic law in conection with lap elements and gharar, as issue of essential. But such still require more study because getting medley it financial instrument types thet ditransaksikan.